Features of Professional Health of a Teacher at Different Stages of Professional Development - Pecherkina, A; Muslumov, R (KnE Life Sciences, 2018)
The article presents the results of a study of the professional health of a teacher at different stages of professional development. 270 school teachers participated in the study. The research methods were selected in accordance with the defined components of the teacher’s professional health: motivational (questionnaire ”Motivation for success” (T. Ehlers), questionnaire ”Motivation to avoid failures” (T. Ehlers)), emotional (questionnaire «Self-assessment of emotional states» (H. Eysenck), questionnaire «Empathy» (A. Mehrabyan)) and reflective (differential reflexivity test (D.A. Leontiev, Y.N. Osin), method of the diagnostic of the development level of reflexivity (A.V. Karpov)). The sample was divided into groups in accordance with the stages of professional development: 0 to 5 years of work experience in school - the adaptation stage; 6 to 15 years - primary professionalization; 16 to 25 years - secondary professionalization; over 25 years – mastery. It is established that the motivational component of a teacher’s professional health is characterized by a moderately high and average motivation for success and a high and very high level of avoidance of failures. The emotional component of a teacher’s professional health is characterized by a low level of frustration and aggressiveness, a high level of anxiety and an average level of rigidity and effective empathy. The reflective component of a teacher’s professional health is characterized by average indicators of the level of development of reflexivity and systemic reflection, as well as low indicators of introspection and quasi-reflection. As professional development occurs, the intensity of the indicators of motivational, emotional and reflective components of a teacher’s professional health changes. It is characterized by increasing motivation for success, increased level of anxiety, increased level of rigidity, development of systemic reflection. Keywords: health, teacher’s professional health, teacher’s professional health structure, motivational component of teacher’s professional health, emotional component of teacher’s professional health, reflective component of teacher’s professional health